2023
DOI: 10.1002/jssc.202201004
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of amino acids and water‐soluble vitamins in a pentylenetetrazole‐induced seizures rat model

Abstract: Epilepsy is a complex neurological disease characterized by spontaneous recurrent seizures that affect around 1% of the global population. Despite the significant progress in the mechanisms of epileptogenesis, there is still about 60% of cases in which the cause is unknown. Thus, revealing the molecular mechanisms of epileptogenesis will greatly improve the development of epilepsy treatment. Since the comprehensive characterization of amino acids and watersoluble vitamins is important in understanding the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Hydrophilic interaction liquid chromatography (HILIC)-MS using amide functionalized columns is the current benchmark in the analysis of underivatized AAs as it provides sufficient retention, good peak shape, and MS compatibility for all AAs [13][14][15]. Recent improvements in AA analysis led to applications in the field of metabolomics [16][17][18] and clinical analysis [19]. However, complex sample matrices can require another separation mode or a more stable column chemistry for robust quantification or method validation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophilic interaction liquid chromatography (HILIC)-MS using amide functionalized columns is the current benchmark in the analysis of underivatized AAs as it provides sufficient retention, good peak shape, and MS compatibility for all AAs [13][14][15]. Recent improvements in AA analysis led to applications in the field of metabolomics [16][17][18] and clinical analysis [19]. However, complex sample matrices can require another separation mode or a more stable column chemistry for robust quantification or method validation.…”
Section: Introductionmentioning
confidence: 99%
“…The method demonstrated the potential to overcome the most common issues in the LC-MS analysis of AAs. Contrary to RPLC [17] or ion-pair chromatography (IPC) [35], neither pre-nor post-column derivatization of the analytes was required. The stationary phase chemistry based on a polymer substrate proved to be robust in terms of retention time and stable under a broad range of eluent compositions, which was a major advantage in comparison to typical HILIC and mixed-mode columns [12,21,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Altered plasma circulating AA levels have been associated with certain types of cancer [1], irritable bowel syndrome [2], and several metabolic disorders. Thus, nowadays, AA profiling finds a great number of applications, from the diagnosis of physiological disorders [3], nutrition research [4], and lately in targeted metabolomics studies [5,6]. Derivatization has been a major issue in AA analysis, given that most traditional detectors (UV, FLR) require the presence of a chromophore group [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, GSH, other thiol metabolites, their derivatives as well as their precursors and intermediates from the GSH biosynthesis pathway are quite polar in nature. They show favorable characteristics for hydrophilic interaction liquid chromatography (HILIC) [30,31]. Not surprisingly, HILIC was therefore the method of first choice in the recent literature using Sulfobetaine and Amide column chemistries [1,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…In one study, Forgacsova et al showed the rapid analysis of 4 thiols by sub-2 μm HILIC-Amide MS/MS in 2.5 min run time. A critical factor in quantitative LC-electrospray ionization-MS (LC-ESI-MS) in the biological matrix is ion suppression and matrix effect (ME), respectively [30]. Stable isotope-labeled internal standards are a good strategy to adequately correct for these MEs.…”
Section: Introductionmentioning
confidence: 99%